Joint response characteristics of AE and PSC in coal rheological-impact process - Wang, Dongming; He, Xueqiu; Wang, Enyuan; Li, Changqing; Li, Dexing; Mao, Zihao (Frontiers in Earth Science, 2025)
A combined monitoring experiment of pressure stimulated currents (PSC) and acoustic emission (AE) signals was conducted on coal samples under the coupled action of rheology and impact load. The temporal response characteristics of AE and PSC were analyzed, and a nonlinear fitting method was used to obtain the functional relationship between AE increment and the number of impacts. Based on the non-extensive statistical mechanics theory, the non-extensive parameter of the PSC decay process was calculated, and the decay law of PSC over time after impact loading was analyzed. The results show that AE and PSC signals can synchronously reflect the deformation and failure behavior of coal samples under rheological and impact loading conditions. During the impact loading stage, both AE counts and PSC signals exhibit a simultaneous surge, demonstrating distinct instantaneous response characteristics. In the subsequent rheological stage, the AE signal manifests as sporadic counts, while the PSC rapidly decays in a power law manner to a stable value. As the rheological stress level and the number of impacts increase, both the maximum and stable values of the PSC exhibit a gradual decreasing trend. The non-extensive statistical mechanics analysis indicates that PSC decay exhibits non-extensive characteristics, with a significant reduction in before impact failure, suggesting that q can be used to assess coal mass stability.